Lesson Learned from Applying Simplified Debate for Critical Thinking and Speaking in Kids Class - Rijoly, Helena Magdalena; Tentua, Freyna Gian Benedict (Prodi Pendidikan Bahasa Inggris, Program Studi Diluar Kampus Utama (PSDKU) Unpatti-MBD, 2021)
An advance Kids English level is created for young learners of elementary school age who have an above average command of English. They have actively used English in real life and in classroom interaction. They are proficient in basic English grammar and the four integrated skills (reading, writing, listening, and speaking). Therefore, the class at LEAP Language Study Centre needed to apply an alternative strategy to enhance and enrich their learning experience. This paper is a descriptive report on the application of simplified debate for Advance Kids Class. The simplified debate application was aimed to achieve three goals: 1) to provide a space for them to continuously and actively practice and use their English under the supervision of the teacher, and 2) to introduce critical thinking. The Advance Kids English C Class adapted a simplified classroom debate to be used for kids aged 11-12 years old currently in 5th and 6th grade of elementary school. This paper presented the result on using debate for kids’ level, detailing how the debate is used in the classroom and the benefit of using the debate in the classroom